ĐÁNH GIÁ ĐỘ NGUY HIỂM ĐỘNG ĐẤT KHU VỰC THÀNH PHỐ HÀ NỘI VÀ LÂN CẬN TRÊN CƠ SỞ THUẬT TOÁN TẤT ĐỊNH MỚI - Tuấn, Thái Anh; Dũng, Lê Văn; Bách, Mai Xuân (Vietnam Journal of Earth Sciences, 2011)
Seismic hazard assessment of Hanoi and adjacent areas on the basis of neodeterministic approach In this paper we would like to present some results of seismic hazard assessments in Hanoi and adjacent areas on the basis of Neodeterministic algorithm. 1. Study area can be divided into 5 source zones and 3 structure zones. Source zones include: (I) with Mmax = 5, (II) with Mmax = 5, (III) with Mmax = 5.3, (IV) with Mmax = 5, (V) with Mmax = 5.6. Structure zones include: South - West relative raise zone, Central lower zone, North - East relative raise zone. 2. The maximum average values of horizontal displacement component (Dmax) changes 4-10cm from South - Western to North - Eastern. The velocity (Vmax) can reach 28 cm/s in North - East zone. The maximum average values of Acceleration (A) can reach: 0.04g < A < 0.11g.